2005
DOI: 10.2174/0929867053362802
|View full text |Cite
|
Sign up to set email alerts
|

Azapeptides as Pharmacological Agents

Abstract: Azapeptides, formed by replacing the C α of amino acid residues by nitrogen, are promising peptidomimetic compounds. Azaamino acids impart a unique conformational property to peptide structures because of the loss of chirality and reduction of flexibility of the parent linear peptide. The peculiar conformational properties make azaamino acids an attractive tool for drug design involving specific secondary structures in peptides and proteins. Additionally, since azapeptides are less susceptible to enzymatic bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…The β-lactam compounds have been considered a possible inhibitor for the elevated expression of gama-SM protein, however, the compounds are not very effective and may produce off-target inhibitory activity, which could point to adverse side effects (65). Another inhibitor that seems to have potentially greater capabilities than β -lactam is Azapeptides, which can constrain cysteine and serine proteases (66, 67). Azapeptides have been modified and tested to obstruct gama-SM protein.…”
Section: Targeting Hsp70 and Gama-sm: A Possible Therapy For Pcamentioning
confidence: 99%
“…The β-lactam compounds have been considered a possible inhibitor for the elevated expression of gama-SM protein, however, the compounds are not very effective and may produce off-target inhibitory activity, which could point to adverse side effects (65). Another inhibitor that seems to have potentially greater capabilities than β -lactam is Azapeptides, which can constrain cysteine and serine proteases (66, 67). Azapeptides have been modified and tested to obstruct gama-SM protein.…”
Section: Targeting Hsp70 and Gama-sm: A Possible Therapy For Pcamentioning
confidence: 99%
“…Investigations in peptide mimicry have also shown that certain structural changes, when introduced into a peptide, can prevent enzyme degradation and induce conformational preferences that mimic the biologically active secondary structure4. Among the modifications found in peptide mimicry, aza‐peptides, in which one or more residue is replaced by an aza‐amino acid5, have found promising utility in enhancing the drug‐like character of peptide candidates6, by increasing the duration of action7 and resistance to enzymatic degradation8, 9 (see Figure 1 for relevant examples). Furthermore, aza‐amino acid residues have been shown to stabilize β‐turn conformations in peptides as detected by computational10–12, spectroscopic13–15 and crystallographic analyses13.…”
Section: Introductionmentioning
confidence: 99%
“…Azapeptides are peptide analogs in which one or more a-carbon atoms have been replaced by a nitrogen atom (Proulx et al, 2011). They can act as protease inhibitors when the replacement affects the a-carbon of the P1 residue in peptide analogs (Adessi and Soto, 2002;Zega, 2005). Azapeptides for the use as protease inhibitors generally contain a P1 aza-amino acid residue and a good reactive leaving group (-ONp, -OCH 2 CF 3 , -OPh), so that they form with the target protease a stable acyl-enzyme intermediate that dissociates very slowly (Zega, 2005).…”
mentioning
confidence: 99%
“…They can act as protease inhibitors when the replacement affects the a-carbon of the P1 residue in peptide analogs (Adessi and Soto, 2002;Zega, 2005). Azapeptides for the use as protease inhibitors generally contain a P1 aza-amino acid residue and a good reactive leaving group (-ONp, -OCH 2 CF 3 , -OPh), so that they form with the target protease a stable acyl-enzyme intermediate that dissociates very slowly (Zega, 2005). The substitution of a carbon by a nitrogen atom at P1 decreases the electrophilicity of the P1 carbonyl group and also moves the geometry of the complex away from a tetrahedron.…”
mentioning
confidence: 99%
See 1 more Smart Citation